PELAKSANAAN MANAJEMEN KURIKULUM PADA MADRASAH TSANAWIYAH KABUPATEN JENEPONTO: (Implementation of Curriculum Management in Madrasah Tsanawiyah, Jeneponto Regency) - Lallang, Hamzah (Uniqbu Journal of Social Sciences, 2022)
The aim of this study is to explain the implementation of curriculum management at Madrasah Tsanawiyah Jeneponto Regency, the formulation of the problem in this study is, how is curriculum management implementation at Madrasah Tsanawiyah Jeneponto Regency? While the research method used for this study will be qualitative. Where the researcher will explain the data in the form of sentences. Meanwhile, the researcher is conducting descriptive research. Whereas the descriptive approach describes only the phenomena, symptoms, events, and events that occur. The results of this study indicate that; to improve the quality of Madrasah Tsanawiyah Negeri Jeneponto Regency, particularly collaborating with the community, both individuals, government, and local organizations for the implementation of quality education and learning, such as: (1) fostering and harmonious cooperative relationships with all educational stakeholders around the madrasah; (3) accommodate and analyze the community's aspirations for ideas, demands, and various educational needs in the form of (a) distributing questionnaires to obtain input, suggestions, and creative ideas from education stakeholders supporting the madrasah; and (b) completing a written report to the community on the results of their observations on the development of education in the area encompassing the madrasah